2017
DOI: 10.1038/cddis.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Notch activation enhances mesenchymal stem cell sheet osteogenic potential by inhibition of cellular senescence

Abstract: Our previous studies have confirmed the therapeutic effects of mesenchymal stem cell (MSC) monolayer sheet transplantation on allograft repair. A limiting factor in their application is the loss of MSC multi-potency as a result of high density sheet culture-induced senescence. In the study reported in this article, we tested whether Notch activation could be used to prevent or delay sheet culture-induced cell aging. Our results showed that, during in vitro long-term (5-day) cell sheet culture, MSCs progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…In other words, Notch activation by Jag‐1 in MSC sheet culture showed decreased cellular senescence and cell cycle arrest. In addition, the in vivo allograft transplantation data revealed a significant increased callus formation (Tian et al, ). In addition, Chakravorty et al () showed that the activation of the Notch signaling pathway in titanium implant surfaces, which have improved osteogenic properties, leads to enhanced osteogenic differentiation as evidenced by a higher expression of osteogenic markers bone sialoprotein and osteocalcin, and bone differentiation factors BMP2, BMP6, and GDF15.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, Notch activation by Jag‐1 in MSC sheet culture showed decreased cellular senescence and cell cycle arrest. In addition, the in vivo allograft transplantation data revealed a significant increased callus formation (Tian et al, ). In addition, Chakravorty et al () showed that the activation of the Notch signaling pathway in titanium implant surfaces, which have improved osteogenic properties, leads to enhanced osteogenic differentiation as evidenced by a higher expression of osteogenic markers bone sialoprotein and osteocalcin, and bone differentiation factors BMP2, BMP6, and GDF15.…”
Section: Introductionmentioning
confidence: 99%
“…Besides proliferation, JAG1 also plays a critical role in the regulation of functional cell death and survival (Regan & Long, ). One recent study from our group clearly showed that JAG1‐induced Notch activation inhibits cellular senescence in mesenchymal progenitor cell cultures (Tian et al, ). In this study, we further analyzed the apoptotic cell death during JAG1‐mediated osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 93%
“…The sequences for each primer pair were as follows: CyclinD1: forward primer, 5′‐ATGGAACATCAGCTGCTGT‐3′ and reverse primer, 5′‐TCAGATGTCCACATCCCGC‐3′; Runx2, forward primer 5′‐CACTGCCACCTCTGACTTCT‐3′ and reverse primer 5′‐CACCATCATTCTGGTTAGGC‐3′; Alkaline phosphatase (ALP): forward primer 5′‐GGGCATTGTGACTACCACTC‐3′, and reverse primer 5′‐AGTCAGGTTGTTCCGATTCA‐3′; Osteocalcin (OC), forward primer 5′‐TGGCCATGCTGACTGCAGCC‐3′, reverse primer 5′‐TGGGTAGGCGTCCCCCATGG‐3′; Bone sialoprotein (BSP), forward primer 5′‐AAGGAACCAAAGCATCAAGAATTAG‐3′ and reverse primer 5′‐AGATGTCATCAGGCAGCTTGAC‐3′; Type I collagen (COl1a1), forward primer 5′‐GTTTGGCCTGAAGCAGAGAC‐3′ and reverse primer 5′‐TCTAAATGGGCCACTTCCAC‐3′; Hey1: forward primer 5′‐GCTCACCCAGACTACAGCTC‐3′ and reverse primer 5′‐ CTCGATGATGCCTCTCCGTC‐3′; Hes1: forward primer 5′‐ TTCCTCCTCCCCGGTGGCTG‐3′ and reverse primer 5′‐TGCCCTTCGCCTCTTCTCCA‐3′; β‐actin: forward primer 5′‐ACCACAGTCCATGCCATCAC‐3′, and reverse primer 5′‐TCCACCACCC TGTTGCTGTA‐3′. The relative expression level of target genes was normalized with geNorm software (Primer Design Ltd) using β‐actin gene as a reference to determine the normalization factor (Tian et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro cell growth was monitored by cell number count and cumulative population doubling time (DT) calculation. DT was examined using the formula: (t − t0) · log2/log (N − N0), where t − t0 is culture time in hours, N is the number of harvested cells, and N0 is the number of cells in the initial seeding …”
Section: Methodsmentioning
confidence: 99%